1998
DOI: 10.1055/s-2007-1001363
|View full text |Cite
|
Sign up to set email alerts
|

Association of Periampullary Diverticula with Primary Choledocholithiasis but not with Secondary Choledocholithiasis

Abstract: The incidence of gallstones was significantly higher in periampullary diverticula, and when the site and the origin of the gallstones was considered the association between diverticula and gallstones was significant in patients with primary common bile duct stones but not with the secondary ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 8 publications
4
29
2
4
Order By: Relevance
“…Advanced age contributes to the development of PD due to weakening of regional connective tissue [9]. A prevalence of 5-32% has been reported in patients undergoing duodenoscopy, and prevalence increases with age and with female gender [1,4,10]. In a study on 350 patients, Zoepf et al reported a PD incidence of 12.5%, and higher average age of patients with PD compared to those without PD [3].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age contributes to the development of PD due to weakening of regional connective tissue [9]. A prevalence of 5-32% has been reported in patients undergoing duodenoscopy, and prevalence increases with age and with female gender [1,4,10]. In a study on 350 patients, Zoepf et al reported a PD incidence of 12.5%, and higher average age of patients with PD compared to those without PD [3].…”
Section: Discussionmentioning
confidence: 99%
“…The variation is due to the different study methods used and the different ages of the subjects investigated. A recent barium study showed a prevalence of 6% [1], and in studies employing endoscopic retrograde cholangiopancreatography (ERCP), it varied between 4.1 and 31.7%, with most around 10–20% [2,3,4,5,6,7,8,9]. On the other hand, a rate of 19.4% has been reported at autopsy [10].…”
Section: Incidence Of Jpdmentioning
confidence: 99%
“…There seems to be no gender predilection. The vast majority of JPD are located on the oral side of the major papilla [9 ](fig. 1).…”
Section: Incidence Of Jpdmentioning
confidence: 99%
“…8 Although a large majority of PAD are asymptomatic, association with various pancreaticobiliary complications is established in the current literature, including increased incidence of choledocolithiasis and pancreatitis. 9,10 This is generally thought to be a consequence of both mechanical compression of the distal CBD as well as dysfunction of the sphincter of Oddi. 9 Thus, radiologists are more permissive of dilated CBD in the presence of PAD when reporting.…”
Section: Introductionmentioning
confidence: 99%